algebra 1
posted by sheirce on .
3/5g+4=6 1/3

If 3/5g+4=6 1/3 mean
3 / ( 5 g ) + 4 = 6 1 / 3
then:
3 / ( 5 g ) + 4 = 6 1 / 3
3 / ( 5 g ) = 6 1 / 3  4
3 / ( 5 g ) = 2 1 / 3
3 / ( 5 g ) = 6 / 3 + 1 / 3
3 / ( 5 g ) = 7 / 3 Multiply both sides by 3
3 * 3 / ( 5 g ) = 7
9 / ( 5 g ) = 7 Mulitiply both sides by g
9 / 5 = 7 g Multiply both sidess by 5
9 = 7 * 5 g
9 = 35 g Givide both sides by 35
9 / 35 = g
g = 9 / 35
If 3/5g+4=6 1/3 mean
( 3 / 5 ) * g + 4 = 6 1 / 3
then:
( 3 / 5 ) * g = 6 1 / 3  4
( 3 / 5 ) * g = 2 1 / 3
( 3 / 5 ) * g = 6 / 3 + 1 / 3
( 3 / 5 ) * g = 7 / 3 Multiply both sides by 3
( 3 * 3 / 5 ) * g = 7
( 9 / 5 ) * g = 7 Multiply both sides by 5
9 * g = 7 * 5
9 g = 35 Divide both sides by 9
g = 35 / 9